A selected review of abstracts from the 20th Annual Meeting of the Society for Neuro-Oncology (SNO). (July 2016) - Chamberlain, Marc C
20th Annual Meeting of the Society for Neuro-Oncology, San Antonio, TX, USA, 18–22 November 2015 The Society for Neuro-Oncology is the largest neuro-oncology meeting in the USA that meets annually and provides a multiday venue that showcases new brain cancer clinical trial results and basic research primarily pertaining to gliomas. The Society for Neuro-Oncology 2015 meeting comprising one education day, 2 days of premeetings and 3 days of presentation, over 200 oral presentations and 900 abstracts provides an overview of contemporary neuro-oncology that includes metastatic disease of the central nervous system as well as primary brain tumors. This review attempts to highlight select abstracts presented at this year's meeting in a short summary that provides a synopsis of a large and multifaceted meeting.